An experimental investigation on fatigue behaviors of HMPE ropes. (15th July 2017) - Lian, Yushun; Liu, Haixiao; Zhang, Yuming; Li, Linan
Abstract: With offshore oil and gas exploration moving into deeper waters, HMPE (high modulus polyethylene) ropes have been widely investigated. However, the tension-tension fatigue behavior of HMPE ropes, especially the effect of mean load on the fatigue life of HMPE ropes, is still lack of sufficient and quantitative understanding. Therefore, to capture the fatigue behavior of HMPE ropes, fatigue tests of HMPE ropes are systematically performed in the present work utilizing a specially designed experimental system. An experimental procedure is proposed and test results show the whole fatigue process of HMPE ropes including tension-time, strain-time and tension-strain curves. The dynamic stiffness of HMPE ropes is also investigated, which shows that it increases with increasing mean load, while decreases with increasing loading amplitude. An empirical expression that accounts for the relationship of the mean load, loading amplitude and fatigue life is proposed to describe the damage evolution of HMPE ropes under long-term cyclic loading. The present work is beneficial to understanding the fatigue resistance ability of HMPE ropes and to application of HMPE ropes in deepwater moorings. Highlights: Whole fatigue process including tension-time, strain-time and tension-strain curves is experimentally obtained. The dynamic stiffness evolution of HMPE ropes with cycles is described. An empirical expression that evaluates effects of mean load and loading amplitude on fatigue lives is proposed.